Corrosion on high-frequency welded Al–1.1Mn–0.5Cu–0.1Ti micro-fin tubes externally cladded with Al–1.2Zn used for high-performance heat transfer applications. (4th July 2022) - Zaffaroni, G. G. B.; Gudla, V. C.; Rizzo, R.; Yazdi, R.; Nordlien, J. H.; Ambat, R.
ABSTRACT: In this study, the corrosion behavior of high-frequency welded micro-fin tubes was investigated using a bi-layered material of Al–1.1Mn–0.5Cu–0.1Ti core alloy with 10% (∼65 µm) one side cladding of Al–1.2Zn alloy. Open-circuit potential, potentiodynamic anodic polarisation tests, zero resistance ammetry (ZRA) measurements, acidified synthetic seawater testing (SWAAT), and full immersion tests were employed to assess the corrosion behaviour of the material. To link the corrosion with microstructural features, scanning electron microscopy and energy-dispersive X-ray spectroscopy, focused ion beam microscopy, and scanning transmission electron microscopy were used. The results showed that the Al–1.2Zn alloy surface sacrificially dissolves, providing cathodic protection to the nobler underlying core material in acidic and neutral environments. Whereas a catastrophic corrosion on the Al–1.1Mn–0.5Cu–0.1Ti core surface (i.e. the devoid of clad surface area of width 220–350 μm) was seen when coupled with Al–1.2Zn in highly alkaline solutions. GRAPHICAL ABSTRACT: UF0001